ANALYSIS OF THE INFLUENCE OF OVERLOADING VEHICLES ON DECREASING THE LIFE OF ROAD PLANS ON RIGID PAVEMENT ON PANTURA ROAD KM 11 TO KM 21, BATANG DISTRICT - Yudaningrum, Farida; Firmansyah, Ekky (Science and Technology Research Centre, Universitas PGRI Semarang, 2023)
Abstract. The north coast road is the main route that connects several provinces, cities, and regencies on the north coast of Java. The road is traversed by many heavy vehicles loaded with goods, so there is the potential for frequent violations caused by excessive loads. Given these problems, this study aims to determine the effect of excessive load on heavy vehicles on decreasing road life.The data used are primary and secondary data, primary data in the form of photos of observations at the Subah Weighbridge and interviews with the head of the Subah Weighbridge, secondary data in the form of actual vehicle weight data from the Subah Weighbridge, LHR, and road age from the National Road Planning Center. Central Java â€“ DI Yogyakarta, then calculate the percentage value of VDF due to overload and decrease in the design life of the road using the vehicle damage factor value using the Bina Marga method (1987).The results of this study indicate that excessive load on heavy vehicles can affect the decrease in road design life. With the actual overload that occurred on Jalan Pantura KM 11 to KM 21, Batang Regency, the cumulative VDF increase based on the Bina Marga method (1987) was 2.63%. The decrease in design life due to actual overload based on the Bina Marga method (1987) was 0.04 years.Â